Sosialisasi dan Penyuluhan Pembagian Warisan berdasarkan Hukum Perdata dan Ilmu Hukum Lainnya di Desa Tumbang Rungan - Achmadi Achmadi; Ratna Atnawatie; Maimunah Maimunah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Diverse problems appear in the lives of the village are definitely wants solving or a solution that as soon as and as soon as possible in order to keep comfort and peace village itself. Responsibility to the various problems arising concerning the interests of the village community of attached to themselves the village head itself. Thus the various problems arising in the village ideally the village head act first as arbiter or umpire to resolve any dispute that occurred. Inheritance already goods of talk about the existence of, the significant events in certain societies, namely the presence of a member of societies or families that have died. A human being as a member of the community, throughout the whole life course, have their place in society with accompanying all the rights and the obligations upon those who were the other members of the community as from the accused and who are in the community. The division of property inheritance often leads to problems in daily life.T his problem often arose because of one of the parties who felt dissatisfied with the division of inheritance he received. This arises from the nature of greedy humans who always desirous to get more of what has been gotten. To get the estate of inheritance in accordance with the number of desired, the heirs traveled every way that can be done to achieve its goal, either through a legal manner and with against the law